Encyclopedic Information in Bilingual Dictionaries: Field of Geography - Valančiauskienė, Aušra (Verbum, 2019)
When preparing a dictionary it is impossible to ignore outside world or so called encyclopedic knowledge. In megastructure level of a bilingual dictionary, various appendices are often addede.g. toponyms, anthroponyms, and ethnonyms. Arranged before or after the corpus, these appendices are most commonly used for grammatical descriptions as well as toponyms (hydronyms and oikonims) and lists of commonly used abbreviations. At the macrostructure and microstructure level, the presentation of encyclopedic knowledge is even more evident: the nomenclature of the modern linguistic monolingual or bilingual dictionary includes a number of lexis related to a particular cognitive domain (ethnography, history, mythology, geography, economics, etc.); therefore, a lot of different encyclopedic information is provided in order to explain it. Recently, many European lexicographers have been discussing the need to avoid any appendices to the vocabulary and to instead incorporate the information contained into the text of lexicographic publication wherever possible. Researchers base this view on the fact that each additional source of information in the dictionary requires further time and energy from the user looking for the lexical unit they want. The user may also be unfamiliar or insufficiently familiar with the dictionary structure and simply be unaware that additional information can be found elsewhere rather than in the dictionary text itself. Thus, the goal of this study is to examine, based on the analytical and descriptive method, four dictionaries published in Lithuania (The Great Lithuanian-English Dictionary (2006), Lithuanian-Russian Dictionary (2015), The Great Lithuanian-French Dictionary (2012) and Lithuanian-Norwegian Dictionary (2001))in terms of geographical knowledge presentation: evaluate the presentation of this knowledge at megastructure, macrostructure and microstructure levels.